2012
DOI: 10.1002/humu.22176
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between Prostate Cancer andMSMBandNCOA4Genetic Variants and Protein Expression

Abstract: Two genome-wide association studies (GWAS) identified the β-microseminoprotein (MSMB) promoter SNP, rs10993994:C>T, as significantly associated with prostate cancer (PC) risk. Follow-up studies demonstrate that the variant allele directly affects expression of the MSMB encoded protein, PSP94, and also suggest that it affects mRNA expression levels of an adjacent gene, NCOA4, which is involved in androgen receptor transactivation. In a population-based study of 1,323 cases and 1,268 age-matched controls, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Following the theory proposed by Laurence [12], the present study provides initial epidemiological support for the hypothesis that the PSP94 protein may inhibit the adverse effects of a sexually transmitted pathogen on prostatic tissue, since men who carry the T allele of rs10993994 have been shown to have lower PSP94 expression in prostate tissue and lower PSP94 concentrations in urine, and are also at increased risk for PCa [6][7][8][9][10][11]. The biological mechanism by which PSP94 may inhibit an STI is unknown.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Following the theory proposed by Laurence [12], the present study provides initial epidemiological support for the hypothesis that the PSP94 protein may inhibit the adverse effects of a sexually transmitted pathogen on prostatic tissue, since men who carry the T allele of rs10993994 have been shown to have lower PSP94 expression in prostate tissue and lower PSP94 concentrations in urine, and are also at increased risk for PCa [6][7][8][9][10][11]. The biological mechanism by which PSP94 may inhibit an STI is unknown.…”
Section: Discussionsupporting
confidence: 71%
“…The PSP94 protein is encoded by the b-microseminoprotein (MSMB) gene. Several studies, including our own [6], have observed that the variant T allele of SNP rs10993994, which is in the proximal promoter region of the MSMB gene, is associated with increased PCa risk and with lower PSP94 protein expression in tissue and urine [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-patient concordance was evaluated on each of the two core samples from the same 2% sample. As previously described, 19 immunostaining was assessed using a score created by multiplying staining intensity (0 for no staining, 1 for light staining, and 2 for strong staining) by the corresponding percentage of cells staining positive at each intensity. The mean score was used for cases with data from duplicate cores.…”
Section: Methodsmentioning
confidence: 99%
“…Fitzgerald et al 38 could find no association between SNPs in this region and overall NCOA4 expression and Rinckleb et al 39 presented data that there is an association of rs10993994 risk homozygosity and DNA repair capacity. Therefore, this PCa GWAS locus is very complex and the association signal may be a combination of very subtle effects on more than one gene/pathway.…”
Section: Genetics and Genomics Of Prostate Cancer M Dean And H Lou 310mentioning
confidence: 99%